The Relationship of Early Maladaptive Schemas, Attributional Styles and Learned Helplessness among Addicted and Non-Addicted Men - Farhad Shaghaghy; Majid Saffarinia; Mohadeseh Iranpoor; Ali Soltanynejad (Addiction and Health, 2011)
Background: Addiction is considered as one of the major problems in family and community in the world. According to cognitive view, organizing the experiences determines how to behave. Due to their importance in interpretation of special situations, cognitive schemas and attributional styles have a significant role in cognitive theories. The aim of this study was to compare early maladaptive schemas and attributional styles in addicts and non-addicts to recognize their role in addiction.Methods: In this causal-comparative study, 200 addicted and non-addicted men were randomly selected. Young early maladaptive schema and attributional styles questionnaires were used. Data analysis was performed by independent t-test, Pearson correlation and regression.Findings: The study population included 81 addicted and 90 non-addicted men. There were significant differences between early maladaptive schemas and attributional styles in the two groups of addicted and non-addicted men (P < 0.001). In addition. addicts had higher levels of learned helplessness. A direct relationship was found between learned helplessness and frequency of addiction treatments (r ═ 0.234, P < 0.05).Conclusion: Our study showed that addicts suffer from high levels of early maladaptive schemas. They had a more pessimistic attributional style. Moreover, addicts who developed higher levels of learned helplessness were less successful in addiction treatment and more likely to use drugs again after treatment. These issues show that addiction institutions and therapists have to pay attention to cognitive factors for addiction prevention.Keywords: Early maladaptive schema, Attributional style, Learned helplessness, Addiction.